KEMITRAAN SEBAGAI STRATEGI USAHA DALAM PERCEPATAN CAPAIAN KESEJAHTERAAN DI KOTA BANDAR LAMPUNG (Survei pada Kelompok UKM Emping Melinjo) - M. Apun Syaripudin (Jurnal Bisnis Darmajaya, 2015)
Bandar Lampung has considerable potential to produce Emping Melinjo, Lampung pretty good natural conditions for growing trees Emping melijo as raw material, it is the primary driving factor Emping Melinjo business grows. Small businesses including chips and drives the economic growth of the community, because it has a very efficient performance, productive also have higher competitiveness.But there are several problems encountered, among others: (1) marketing, (2) capital, (3) innovation and utilization of information technology, (4) the supply of raw materials, (5) and the empowerment of labor absorption, and (6) plans business development. Deals with the problems faced, the strategies needed to overcome them. Business development chips, certainly not enough to simply charged to the business itself, but there should be good support from stakeholders, business associations, universities, and related institutions. In addition, government policy is required which leads to the business development efforts of society, so the achievements realized in optimal social welfare.Keywords: Partnership, Strategy, Welfare